2008
DOI: 10.1097/bsd.0b013e31815ecc4b
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Sacroiliac Arthrodesis

Abstract: Minimally invasive sacroiliac arthrodesis via a percutaneous posterior approach is a safe and efficacious procedure, leading to a high fusion rate and significant improvement in low back, leg pain, and dyspareunia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
102
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(113 citation statements)
references
References 24 publications
3
102
0
2
Order By: Relevance
“…Some studies have found up to 22.5 % of referred nonspecific back pain to be sourced to the sacroiliac joint [1]. Although it is prudent to exhaust all nonsurgical means in the treatment of sacroiliac joint pain, there remains a group of patients who do not improve without surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found up to 22.5 % of referred nonspecific back pain to be sourced to the sacroiliac joint [1]. Although it is prudent to exhaust all nonsurgical means in the treatment of sacroiliac joint pain, there remains a group of patients who do not improve without surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous iliosacral screw fixation has long been considered a safe and predictable treatment for the management of disrupted sacroiliac joints with unstable pelvic ring injuries [3]. The use of percutaneous iliosacral screw fixation as a treatment of sacroiliac joint pain has been reported to be successful [1,4,5], however, these studies have small patient numbers. We have been undertaking elective percutaneous sacroiliac joint stabilisation in our institution for several years, and we report our experience in using this technique.…”
Section: Introductionmentioning
confidence: 99%
“…Among all the conservative options available a recent review showed poor short-term and long-term results from intra-articular or peri-articular injections with steroids or botulin toxin, pulsed radiofrequency, and conventional radiofrequency neurotomy, with slightly better results with cooled radiofrequency neurotomy [3]. In recent years several groups have reported excellent results with SI joint fusion [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. With the hypothesis that surgical treatment will show excellent results we report a prospective series of 24 patients, after following a diagnostic and therapeutic algorithm [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of significant complications after open SIJ fusion has been reported to be between 6 and 25 % [74,75]. Recently, a percutaneous sacroiliac procedure has also been reported [76,77]. This technique enables arthrodesis by inserting bone material in the cagetype screw and may avoid wound-related complications.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Seven patients were found to have symptomatic non-union, with union occurring only in six. Wise and Dall [76] reported on the efficacy and outcomes of minimally invasive SIJ arthrodesis in 13 patients via a percutaneous posterior approach (8 of the 13 patients had a history of a lumbar fusion that extended to the sacrum). Wise and Dall [76] used percutaneous insertion of threaded titanium cages packed with recombinant human bone morphogenetic protein-2 (rhBMP-2) into the SIJ.…”
Section: Surgical Treatmentmentioning
confidence: 99%